คุณภาพชีวิตการทำงานของพนักงานศูนย์ศรีพัฒน์ คณะแพทยศาสตร์ มหาวิทยาลัยเชียงใหม่ - อัมพวัน คันธรส (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purposes of this independent study were to study the factors that affected the working life quality and to study the working life quality of employees at Sriphat Medical Center, Faculty of Medicine, Chiang Mai University. The study was based on the working life quality concept of Management System of Quality of Work Life (MS-QWL), The Human Capacity Building Institute, Federation of Thai Industries. The data was collected from 234 officers. The data was then analyzed by descriptive statistics, e.g., frequency, percentage, mean, as well as inferential statistics, e.g., t-test, one-way ANOVA analysis, Least Significant Difference, Correlation Analysis and Multiple Regression Analysis.